2004
DOI: 10.1124/jpet.103.061812
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Drug-Drug Interactions between Methotrexate and Nonsteroidal Anti-Inflammatory Drugs in the Renal Uptake Process Based on the Contribution of Organic Anion Transporters and Reduced Folate Carrier

Abstract: The present study examined the possible role of transporters in the drug-drug interactions between methotrexate (MTX) and nonsteroidal anti-inflammatory drugs (NSAIDs) in the renal uptake process of MTX. MTX is recognized by reduced folate carrier (RFC-1) and rat organic anion transporters (rOat1 and rOat3) as a substrate. Uptake of MTX by kidney slices was saturable and inhibited potently by dibromosulfophthalein. Folate and benzylpenicillin (PCG) inhibited the uptake by 30 to 40% and 40 to 50% of the total s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 29 publications
(34 reference statements)
2
56
0
Order By: Relevance
“…Renal tubular secretion involves different uptake transporters. A recent study showed that the basolateral localization of mouse reduced folate carrier (RFC-1) in the kidney is responsible for the uptake of MTX (Nozaki et al, 2004). Other uptake transporters that are mainly expressed in the liver (OATP1B) or intestine (OATP1A2) were found to transport MTX in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Renal tubular secretion involves different uptake transporters. A recent study showed that the basolateral localization of mouse reduced folate carrier (RFC-1) in the kidney is responsible for the uptake of MTX (Nozaki et al, 2004). Other uptake transporters that are mainly expressed in the liver (OATP1B) or intestine (OATP1A2) were found to transport MTX in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Multidrug resistance-related proteins (MRP) 2 and 4 and breast cancer-resistant protein (BCRP) transport MTX across the apical membrane into the urine where it is excreted. [12][13][14][15] Previous studies have shown that several mechanisms, including the inhibitory effect of NSAIDs on OATs and RFC-1-mediated MTX uptake at the basolateral membrane, 16,17) and MTX efflux via MRP2 and MRP4 at apical membrane in tubular cells, 18) are involved in the interaction between MTX and NSAIDs.…”
mentioning
confidence: 99%
“…Renal tubular secretion and reabsorption of folates in proximal tubules involves specific roles for folate transporters on the basolateral (e.g., OAT1, OAT3, RFC) and apical (e.g., OATP1, FR , MRP2, MRP4) membranes Nozaki et al, 2004). Folates are filtered via the glomerulus and reabsorbed by a FR -mediated endocytotic process, then transported into the bloodstream by folate transporters localized to the basolateral membrane.…”
Section: Folate Transport In Tissue Folate Homeostasis and Physimentioning
confidence: 99%